2017
DOI: 10.1002/sctm.16-0447
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Fetal Membranes in Regenerative Medicine: New Tricks from an Old Dog?

Abstract: The clinical application of the fetal membranes dates back to nearly a century. Their use has ranged from superficial skin dressings to surgical wound closure. The applications of the fetal membranes are constantly evolving, and key to this is the uncovering of multiple populations of stem and stem‐like cells, each with unique properties that can be exploited for regenerative medicine. In addition to pro‐angiogenic and immunomodulatory properties of the stem and stem‐like cells arising from the fetal membranes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 110 publications
1
22
0
1
Order By: Relevance
“…Owing to their immunosuppressive properties, intact FMs and the decidua have been studied for their potential application for tissue engineering and cell therapies. FMs consist of a number of cell types, 18-20 and our data showed the presence of mesenchymal and epithelial cells. Some hematopoietic cells are also observed in the FMs, primarily consisting of macrophages (Hofbauer cells).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Owing to their immunosuppressive properties, intact FMs and the decidua have been studied for their potential application for tissue engineering and cell therapies. FMs consist of a number of cell types, 18-20 and our data showed the presence of mesenchymal and epithelial cells. Some hematopoietic cells are also observed in the FMs, primarily consisting of macrophages (Hofbauer cells).…”
Section: Discussionsupporting
confidence: 59%
“…Similar to our findings, previous studies have shown that cellular components of membranes surrounding the fetus produce high levels of IL-6 and IL-10 and suppress IFNγ secretion in MLRs. 18,27-31 These cytokine effects are believed to support the immunosuppressive and tolerogenic environment at the feto-maternal interface. Interestingly, in the alloantigen and mitogen stimulated T-cell cultures, we observed an association between the increase in the number of membrane cells to the decrease in the production of IFNγ, TNFα, IL-2, and IL-4.…”
Section: Discussionmentioning
confidence: 99%
“…The population of MSC can express CD105 (Endoglin), CD73, and CD 90 (Thy-1) of ≥95% as measured by cytometry flow. There was a lack of CD45, CD34, CD14 or CD11b, CD79α or CD19, and HLA Class II expressions (≤2% positive) and MSC must be multipotent differentiated into osteoblasts, adipocytes, and chondroblasts under in vitro standard conditions [16], [17].…”
Section: Discussionmentioning
confidence: 99%
“…This capacity of stem cells to exert an immunomodulatory action has been described in many in vitro and in vivo studies, but unfortunately, the immunological consequences of stem cells transplantation are still uncertain and affect the planning of clinical trials. Fetal cells are not rejected by the maternal immune system; although the mechanisms that underlie the acceptance of the fetal allograft are not completely understood [15], it is well known that the placenta plays an important role in modulating the maternal immune system during pregnancy [17]. The paradox of maternal tolerance was first analyzed by Peter Medawar in 1953, who proposed that (i) there is a physical separation between the fetus and the mother; (ii) the fetus is antigenically immature; and (iii) the mother has immunological inertia [15].…”
Section: Development Of Embryonic and Fetal Annexesmentioning
confidence: 99%